Problematika Wanita Dalam Melaksanakan Puasa Ramadhan - Tjek Tanti (Jurnal Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2017)
Indications are that the person who made it to the pious fasting Ramadan fasting can be seen from the spirit filling the days of Ramadan by fasting in addition to various forms of worship, such as the praying tarawih qiyamullail, Witr prayer, Tahajjud prayers, recitations of the Qur'an, charity and various other good deeds , in addition to marked post-Ramadan Islamic dengankehidupan.   Kata kunci: Problematika, wanita, puasa, Ramadhan, pelaksanaan